Effects of AlInN graded polarization-dependent doped top cladding on the performance of deep ultra-violet laser diode emitting at ∼271 nm wavelength. (11th November 2020) - Paliwal, Avinash; Singh, Kuldip; Mathew, Manish
Abstract: This work presents the theoretical study on the polarization induced p-type doping of undoped-AlInN graded cladding layers for the deep ultra-violet laser diode (LD) emitting at around 271 nm wavelength. The reference LD consists of 320 nm of linearly graded undoped AlN-Al0.7 Ga0.3 N layer, while in our LD the graded undoped AlN-Al0.7 Ga0.3 N layer is replaced by the undoped AlN-Al x In(1− x ) N composition graded layers with different x mole fraction from 0.88 to 0.92. The static device resistance for reference LD is ∼28.6 Ω which is reduced to ∼18.38 Ω for AlN-Al0.12 In0.88 N graded layer at 500 mA. The device resistance has been reduced dramatically by ∼10.2 Ω. The reduction in resistance is attributed to the increased polarization grading in AlN-Al0.12 In0.88 N. The large polarization grading leads to large hole carrier induction in the layer which increases the p-type conductivity of the undoped AlN-Al0.12 In0.88 N graded layer. Threshold current for reference LD is 393 mA which has been reduced to 384 mA for AlN-Al0.12 In0.88 N. The electron leakage has reduced from 0.9 kA cm −2 to 0.11 kA cm −2 at ∼30 kA cm −2 injected current density, whereas the hole transportation has improved from 29.23 kA cm −2 to ∼30 kA cm −2 at ∼30 kA cm −2 injected current density.